Relationship Between Students’ Prior Academic Achievement and Homework Behavioral Engagement: The Mediating/Moderating Role of Learning Motivation - Rodríguez, Susana; Núñez, José C.; Valle, Antonio; Freire, Carlos; Ferradás, María del Mar; Rodríguez-Llorente, Carolina (Frontiers in Psychology, 2019)
The interest of assigning homework is frequently discussed due to its alleged low impact on student achievement. One of the current lines of research is to emphasize the quality of student homework engagement rather than the amount of time spent on homework. The aim of this study was to determine (a) the extent to which students’ prior achievement affects their homework engagement (i.e., time spent, time management, and amount of teacher-assigned homework done), and (b) how students’ intrinsic motivation towards homework may mediate or moderate the relationship between prior achievement and the homework engagement variables. A large sample of students from the first four years of Secondary Education (N = 1899) completed questionnaires. The results showed that intrinsic motivation partially mediates, but does not moderate, the effect of prior achievement on the three variables related to homework engagement (time spent, time management, and amount of teacher-assigned homework done). These results highlight the importance of considering both students’ current level of achievement and their motivation towards homework engagement when assigning homework.